Pemberlakuan Karantina Wilayah/Lockdown sebagai Upaya Perlindungan Masyarakat pada Kondisi Darurat Kesehatan: Kebijakan Responsif atas Eskalasi Kasus Covid-19 - Christian Todo; Desak Putu Risma Widyantari; Rahmat Akbar Berliano Ulurura (Jurnal Hukum Lex Generalis, 2022)
The pandemic that has lasted for more than two years has prompted various countries to impose Lockdown Policy as a preventive and limited action against the spread of the Covid-19 virus which continues to grow massively and create new variants. The discourse also spreads within society which raises controversy in regard to the policy. The government through legislative efforts has tried to implement policies in the form of Large-Scale Social Restrictions and the Enforcement of Restrictions on Community Activities. However, since the two regulations were enacted, Indonesia has not been off from the Pandemic status, hence it is necessary to conduct a policy that can bring Indonesia to recover both health and economically by taking into account the Presidential Decree of Republic of Indonesia Number 12 of 2020 of Non-Natural Disasters of the Spread of Corona Virus Disease (COVID-19) as a National Disaster and the responsibility of the state in protecting its citizens. This paper will discuss Indonesia's position on the discourse of implementing the Regional Quarantine/Lockdown which is strengthened by outlining the theoretical substance related to the justification of the state, and local government and the implications for its implementation.